Lung cancer with superior vena cava syndrome diagnosed by intravascular biopsy using EBUS-TBNA. (2016) - Lee, Daegeun; Moon, Seong Mi; Kim, Dongwuk; Kim, Juwon; Chang, Haseong; Yang, Bumhee; Jeong, Suk Hyeon; Lee, Kyung Jong
Abstract: Since superior vena cava syndrome (SVCS) is a critical condition, immediate diagnostic approach and therapy are imperative to avoid potentially life-threatening complications. Here, we report a case of lung cancer with SVCS, which was diagnosed through intravascular tumor biopsy using endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). EBUS-TBNA enabled us to obtain tissue sufficient for diagnosis, without significant complications. Prompt diagnosis was followed by appropriate anticancer treatment and improvement in the symptoms. For patients suspected of SVCS and requiring prompt pathologic diagnosis, we can consider EBUS-TBNA to diagnose intravascular or mediastinal tumors and provide an accurate diagnosis.